Clinical and MRI characteristics of multiple sclerosis in patients of Middle Eastern and North African ancestry residing in Ontario, Canada. (June 2021) - Seyman, Estelle; Jones, Ashley; Guenette, Melanie; Vosoughi, Reza; Selchen, Daniel; Amezcua, Lilyana; Baral, Stefan; Oh, Jiwon
Background: Multiple sclerosis (MS) incidence is rising in traditionally low-burden regions, including the Middle East and North Africa (MENA). Objectives: Our objective was to evaluate disease characteristics in MS patients of MENA descent (MENA-MS). Methods: MENA-MS patients and age- and sex-matched MS patients of European descent (EUR-MS) were identified through the MS Clinic Registry of St. Michael's Hospital in Toronto, Canada. Disease activity and severity were evaluated by the annualized relapse rate (ARR), magnetic resonance imaging (MRI) activity, change in the Expanded Disability Status Scale (EDSS), progression index (PI), and MS Severity Score (MSSS). Results: All MS patients within the registry identified to be of MENA origin ( n  = 192), and age- and sex-matched EUR-MS patients were included. Mean age was 42.9 years, 67% female. A total of 25% and 24% of EUR-MS and MENA-MS had progressive disease, with similar mean disease durations (11.5 and 11.4 years, respectively). Clinical and radiological disease activity (ARR, proportion with new/enlarging MRI lesions) was similar. MENA-MS showed greater disability progression over time (EDSS change = 0.24 vs. 0.06, p  = 0.01), a higher MSSS (3.12 vs. 2.67, p  = 0.04), and higher PI (0.34 vs. 0.27, p  = 0.07). Conclusion: MENA-MS patients demonstrate higher disease severity compared to EUR-MS patients, despite having similar inflammatory measures of disease activity, with disability progression in the absence of relapses. These observations illustrate the importance of the intersections of environmental, socioeconomic, and genetic determinants in optimizing individualized MS care.